The Ways of Modelling and Forecasting Profit Tax Revenue in Lithuania - Mačiulaitytė, Elena (Ekonomika, 2006)
The aim of this paper is to propose the ways of profit tax revenue modelling and forecasting when changes of the legitimate order are considered in time series modelling. To this end, profit tax-related legislative changes are reviewed in the first part of the paper. The basic elements of the profit tax, such as the tax object, subject, the order of carryover of losses, tax rates, methods of computing a profit tax advance payment, due dates of a yearly profit tax have been changed several times over the period of profit tax application. The second part of the paper presents the stages of profit tax revenue modelling. At the first stage, the indicator of profit is suggested to be modelled and forecast using a linear regression of economic indicators. At the second stage, the function of profit tax revenue, depending on the profit indicator and other different legitimate elements of profit tax, has to be found.